A new model of the mechanism underlying lead poisoning: SNPs in miRNA target region influence the δ-aminolevulinic acid dehydratase expression level. (November 2017) - Li, Chunping; Wang, Miaomiao; Wang, Yiqing; Zhang, Jinlong; Sun, Na
Aim: To determine if SNPs located within the 3′-UTR of δ-aminolevulinic acid dehydratase (ALAD) can alter the risk of lead poisoning and the ALAD gene expression.Materials & methods: A case–control study was carried out to find the SNPs in miRNA target region. Luciferase reporter gene assay, qRT-PCR and Western blot was used to determine the relationship between miRNA and SNPs.Results: We found a significant association between rs818708 and the risk of lead poisoning. miR-545–5p was influenced by rs818708 variant and might result in a significant change in ALAD expression.Conclusion: rs818708 T > C can weaken the binding capability between miR-545–5p and 3′-UTR of ALAD and thus may alter the risk of lead poisoning.